Exploring the Mechanism of Zhibai Dihuang Decoction in the Treatment of Ureaplasma Urealyticum-Induced Orchitis Based on Integrated Pharmacology - Bin, Dong-hua; Zhang, Shi-ying; Zhan, Min; Li, Ling; Li, Ying-qiu; Zhou, Xing; Lu, Fang-guo; Zhou, Qing; He, Qing-hu (Frontiers in Pharmacology, 2021)
Background: Ureaplasma urealyticum (UU) infection is the most common cause of male infertility. Zhibai Dihuang Decoction (ZBDHD) can improve the rate of forwarding motility sperm, sperm deformity rate, seminal plasma zinc and refined berry sugar levels. Methods: The potential targets of ZBDHD are obtained from The Encyclopedia of Traditional Chinese Medicine (ETCM). Orchitis-related targets were collected from the Genecards and OMIM databases. The Cytoscape and the Database for Annotation, Visualization and Integrated Discovery (DAVID) were utilized to construct and analyzed the networks. Finally, a rat model of orchitis caused by UU infection was used to detect related indicators of mitochondrial energy metabolism using TUNEL apoptosis detection technology, loss cytometry, Real-Time Quantitative Reverse Transcription PCR (qRT-PCR) and Western Blot. Results: A total of 795 ZBDHD targets and 242 orchitis-related targets were obtained. The “ZBDHD- orchitis PPI network” was constructed and analyzed. ZBDHD can regulate signaling pathways and biological processes related to mitochondrial energy metabolism. The results of experimental studies have shown that ZBDHD maintains the integrity of sperm mitochondrial respiratory chain function by enhancing mitochondrial Na+-K+-ATPase and Ca2+-Mg2+-ATPase activities, promotes the synthesis of mitochondrial ATP, and improves sperm energy supply, thereby improving the motility, vitality and survival rate of sperm, and effectively improving the quality of semen in UU-infected rats (p < 0.05). Conclusion:This study discovered the multi-pathway mechanism of ZBDHD intervention in UU-induced orchitis through integrated pharmacological strategies, which provides a reference for further research on the mechanism of ZBDHD intervention in orchitis in the direction of mitochondrial energy metabolism.